2015
DOI: 10.1063/1.4906061
|View full text |Cite
|
Sign up to set email alerts
|

Mobility enhancement in polymer organic semiconductors arising from increased interconnectivity at the level of polymer segments

Abstract: We present a model to estimate the mobility in polymers and to gauge the effect of increased interconnectivity at the level of polymer segments. The model takes into account the finite length of the polymers and the two-dimensional nature of the transport. These results show that the presence of polymer segments extending from one ordered domain into another can enhance the mobility significantly provided the π-π coupling is sufficiently large.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Those authors explain the high mobility by the ability of some molecules to connect ordered regions between them like a wire. Simulations have been performed to show the increase of the mobility with the increase of the polymer interconnections . If all ordered regions were interconnected the transport mechanism should be a band‐like transport.…”
Section: Transport Properties and Mobility Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those authors explain the high mobility by the ability of some molecules to connect ordered regions between them like a wire. Simulations have been performed to show the increase of the mobility with the increase of the polymer interconnections . If all ordered regions were interconnected the transport mechanism should be a band‐like transport.…”
Section: Transport Properties and Mobility Modelsmentioning
confidence: 99%
“…Simulations have been performed to show the increase of the mobility with the increase of the polymer interconnections. 46,47 If all ordered regions were interconnected the transport mechanism should be a band-like transport. However, the possible presence of subconjugation units in the long polymer chains could introduce traps, explaining the mobility behavior according to the MTR model.…”
Section: Molecular Crystals With Trapsmentioning
confidence: 99%
“…The next step is to bring the stacking inter‐chain spacing to <3.5 Å and increase the electronic coupling between backbones; i.e., expand the dominating 1D states into 2D states. Bao and co‐workers have demonstrated that a metastable crystalline state of TIPS‐pentacene with surprisingly small stacking interval 3.08 Å can enhance the performance greatly, compared to a polymorphic structure with 3.33 Å interval; the exponential increase of co‐facial overlap between π–π stacking transfer integral plays an important role . Therefore, control the crystallization to bring backbones closer and/or the design of new molecular structures to suppress steric constraints is an important step for new semiconducting polymers.…”
mentioning
confidence: 99%
“…Equally important is the anisotropy of their molecular geometry . These two aspects combine to yield strongly anisotropic electronic properties at the molecular level—charge transfer integrals are largest along the polymer chain's backbone, followed by those of π‐stacked segments of different chains, and with negligible orbital overlap along the direction in which the solubilizing side chains interact . Furthermore, weak dielectric constants and strong electron–phonon interactions in conjugated polymers mean that charge in these materials is transported by polarons.…”
Section: A Unique Mode Of Charge Transport Which Requires Optimizatiomentioning
confidence: 99%
“…In these soft optoelectronic materials, special attention has been paid to a variety of structural features and the large effects they have on charge transport. It has thus been found that polycrystalline small molecule films are sensitive to grain boundaries; semicrystalline and partially ordered polymers are strongly affected by π‐stacking in the ordered phase and bridging chains that traverse the disordered phase; and amorphous materials are limited by slow hopping between randomized intermolecular orientations . Static spatial concerns are not alone, as soft materials are also sensitive to vibrations that can modulate the electronic connectivity between subunits on time scales comparable to charge transfer .…”
Section: Introductionmentioning
confidence: 99%